Odpowiedzi

Najlepsza Odpowiedź!
2009-11-25T19:58:13+01:00
A)-7x
b)1 ,1/6x -2,1/3xy
c)-3x^2-y^2
d)-x
e)-3x+3,1/2
f)-6ab-4a
2009-11-25T20:01:13+01:00
A)-4x-7-3x+7=-7x
b)x-2xy+½x-1/3x-1/3xy=x-2xy+3/6x-2/6x-1/3xy=5/6x-2 1/3 xy
c)-x²+y²-2x²-2y²=-3x*-y*
d)-x²+2x-3x+x²=-x
e)4x+4-7x-½=-3x=3 1/2
f)-2ab+12a-4ab-16a=-6ab-4a
2009-11-25T20:16:21+01:00
Rozwiązanie:

-4x-7-3x+7=-7x
x-2xy+1/2 x-1/3 x-1/3 xy=x+3/6 x+2/6 x-2 1/3 xy=1 5/6 x-2 1/3 xy
-x²+y²-2x²-2y²=-〖3x〗^2-y^2
-x²+2x-3x+x²=-x
4x+4-7x-1/2=-3x+3 1/2
-2ab+12a-4ab-16a=-6ab-4a